Childhood maltreatment and violent delinquency in Chinese juvenile offenders: Callous-unemotional traits as a mediator. (July 2021) - Chang, Shumin; Hou, Qingqing; Wang, Chengyi; Wang, Meifang; Wang, Lingxiao; Zhang, Wenxin
Highlights: Childhood sexual abuse had direct and indirect effects on juvenile violent delinquency. CU traits mediated between childhood sexual abuse and juvenile violent delinquency. CU traits mediated between childhood emotional neglect and juvenile violent delinquency. CU traits did not mediate between physical abuse and juvenile violent delinquency. CU traits significantly predicted juvenile violent delinquency. Abstract: Background: Adolescents in China suffer a high prevalence of childhood maltreatment, which has been shown to facilitate juvenile violent delinquency. Studies have implicated a relationship between callous-unemotional traits and both juvenile violent delinquency and childhood maltreatment. However, the complex relationships among these three variables have not yet been examined. Objective: This study aimed to investigate the mediating role of callous-unemotional traits in the relationship between different types of childhood maltreatment and juvenile violent delinquency. Participants and setting: Childhood maltreatment and callous-unemotional traits were assessed in a sample of 441 juvenile violent offenders and a control group of 543 non-offenders, using questionnaires. Methods: After controlling for socio-economic status, a mediation analysis determined the direct, indirect, and total effect of the mediation of callous-unemotional traits in the relationship between childhood maltreatment and juvenile violent delinquency. Results: The results showed no mediation of callous-unemotional traits in the relationship between physical abuse and juvenile violent delinquency. However, callous-unemotional traits mediated the relationship between sexual abuse and juvenile violent delinquency as well as between emotional neglect and juvenile violent delinquency. Conclusions: Our findings suggest that sexual abuse has both a direct and indirect effect on juvenile violent delinquency via callous-unemotional traits, whereas childhood emotional neglect had only an indirect effect on juvenile violent delinquency.